A rare endemic land-snail from Argentina: Plagiodontes rocae Doering 1881 (Gastropoda: Orthalicidae: Odontostominae) - Piza, Julia (2006)
Plagiodontes rocae Doering 1881 is a strictly endemic species from the Paleozoic mountains of southern Buenos Aires province (Argentina). Its identity has been never controversial, but its description and discrimination from related species was still incomplete. A quantitative analysis of its measurements was advisable to locate the species in the frame of a morphological re-analysis of all species in genus Plagiodontes Doering1876. In this study, Protoconch sculpture is illustrated by SEM micrographs to rectify previous descriptions. Shell measurements and angles are studied by Multivariate Discriminant Analysis to discriminate it from other small-sized species. Genital anatomy of P. rocae is described for the first time, its quantitative data being discriminated by multivariate methods from those of the only co-existing Odontostominae, i.e., Plagiodontes pat-agonicus.